MALAYSIA-INDONESIA COOPERATION ESSENTIAL IN THE ADVANCEMENT OF ASEAN S&T AGENDA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 17 November 2015 – Malaysia and Indonesia need to strengthen the cooperation in the field of Science and Technology to face major challenges in the future.